Os feitos de D. Fuas Roupinho na 'Crónica de 1419' - Tiago João Queimada e Silva (Institute of Economic and Social History in the Faculty of Arts of the University of Coimbra, 2022)
This study focuses on two specific chapters of the 1419 Crónica de Portugal (Chronicle of Portugal), dedicated to D. Fuas Roupinho’s heroic deeds. I made a thorough examination of the chronicle’s narratives where he played the leading role, aiming at a better understanding of the functionality that these reports incorporate, when framed in the global political-ideological purposes of the fifteenth century royal chronicles. On the other hand, I tried to draw up a short report on the state of the art regarding the recent process of making credible the historic character of D. Fuas Roupinho, initiated by a number of contemporary historians, and provide a general context of the historical background that has served as raw material for the formation of the account of the 1419 Chronicle, making use of elements revealed by other researchers. Finally, I tried to unveil new data on the supposed historical identity of the mythical Lusitanian “admiral”.